HUBUNGAN TINGKAT KEGAWATDARURATAN DENGAN WAKTU TANGGAP PERAWAT TERHADAP PENANGANAN PASIEN DI IGD RSUD KOTA DUMAI - Melissa " Meliany; Misrawati " "; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractEmergency is a condition where someone needs help right away, this is because if it does not get help immediately life-threatening or cause permanent disability. In this indispensable response time is fast and precise in the management of patients in the ER (emergency room). This study aims to determine the relationship between emergency level and nurses’ time response to handkle patients in the IGD RSUD Kota Dumai with descriptive research design correlation and cross sectional approach. Samples were 27 nurses on duty in the IGD RSUD Kota Dumai. Using total sampling technique. Measuring instrument used in this study is the observation sheet. The analysis used univariate analysis to determine the frequency distribution and bivariate analysis using chi square test and Kolmogorov-Smirnov test. The results showed that most of the nurses in the IGD RSUD Kota Dumai aged 18-40 years (88.9%), female (66.7%), the last graduates D3 (88.9%), have a work experience <5 years (55.6%), with the majority of cases are in the category of Urgent (yellow), and the majority of the response time of <5 min (70,4%). The results of the bivariate analysis research showed that there is a relationship between the level of emergency to response time nurses (p value 0.001). Suggested to the nurse to increase response time and performance in handling emergency patients. Keywords: IGD, the level of emergency, response time nurse.